2004
DOI: 10.1051/0004-6361:20040558
|View full text |Cite
|
Sign up to set email alerts
|

Balmer lines as T$\mathsf{_{eff}}$ and log g indicators for non-solar composition atmospheres

Abstract: Abstract.Although the importance of a correct abundance assumption in the determination of effective temperature and surface gravity of a star has been demonstrated in the literature, this determination is often still extremely simplified, neglecting the effects of non-solar chemical abundances. In this paper we show how the modeling of the profiles of H δ and H γ , commonly used as T eff and log g indicators, is affected when the chemical composition is far from the standard one. As a target for our study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
7
28
0
Order By: Relevance
“…Table 3 is that obtained from the region longward of the Balmer discontinuity. Its value is the same as that presented by Catanzaro et al (2004 Zirconium: no Zr lines were observed in the spectrum. They are not predicted by assuming solar Zr abundance.…”
Section: The Resulting Abundancessupporting
confidence: 76%
See 4 more Smart Citations
“…Table 3 is that obtained from the region longward of the Balmer discontinuity. Its value is the same as that presented by Catanzaro et al (2004 Zirconium: no Zr lines were observed in the spectrum. They are not predicted by assuming solar Zr abundance.…”
Section: The Resulting Abundancessupporting
confidence: 76%
“…Helium: from the analysis of the He i lines 4713 Å and 5875 Å, Catanzaro et al (2004) derive an underabundance of (Bonifacio et al 1995). This kind of anomalous profiles was interpreted as evidence of helium stratification (Dworetsky 2004;Bohlender 2005).…”
Section: The Resulting Abundancesmentioning
confidence: 99%
See 3 more Smart Citations